2015
DOI: 10.3347/kjp.2015.53.5.653
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Tick-Borne Pathogens in the Korean Water Deer (<i>Hydropotes inermis argyropus</i>) from Jeonbuk Province, Korea

Abstract: The objective of this study was to investigate the prevalence of tick-borne pathogens in the Korean water deer (Hydropotes inermis argyropus). Pathogens were identified using PCR which included Anaplasma, Ehrlichia, Rickettsia, and Theileria. Rickettsia was not detected, whereas Anaplasma, Ehrlichia, and Theileria infections were detected in 4, 2, and 8 animals, respectively. The most prevalent pathogen was Theileria. Of the 8 Theileria-positive animals, 2 were mixed-infected with 3 pathogens (Anaplasma, Ehrli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The most important concern with regard to Korean water deer is that these animals are frequently exposed to ticks in mountainous regions and are naturally infected with TBPs and are thereby more likely to transmit TBDs not only to humans but also to livestock in the ROK. To date, several studies have shown that Korean water deer have become infected with various TBPs, and most of which were zoonotic pathogens (Seong et al 2015, Han et al 2017, Amer et al 2019). This study revealed that A. phagocytophilum, A. capra, B. capreoli, and C. burnetii were detected in Korean water deer, indicating that Korean water deer are reservoir hosts for zoonotic TBPs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most important concern with regard to Korean water deer is that these animals are frequently exposed to ticks in mountainous regions and are naturally infected with TBPs and are thereby more likely to transmit TBDs not only to humans but also to livestock in the ROK. To date, several studies have shown that Korean water deer have become infected with various TBPs, and most of which were zoonotic pathogens (Seong et al 2015, Han et al 2017, Amer et al 2019). This study revealed that A. phagocytophilum, A. capra, B. capreoli, and C. burnetii were detected in Korean water deer, indicating that Korean water deer are reservoir hosts for zoonotic TBPs.…”
Section: Discussionmentioning
confidence: 99%
“…K orean water deer (Hydropotes inermis argyropus) are widespread and are the most commonly rescued wild animals in the Republic of Korea (ROK) (Seong et al 2015). The Korean water deer has been classified as a vulnerable species and is included in the International Union for Conservation of Nature and Natural Resources Red List worldwide, except the ROK.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frozen blood samples were thawed at room temperature and genomic DNA was extracted from 200 µl of blood using a Magpurix ® Blood Kit and Magpurix ® 12s automated nucleic acid purification system (Zinexts Life Science Corp., Taipei, Taiwan), according to the manufacturer's recommendations. DNA preparations were tested for the presence of Anaplasma species by PCR/ sequence analysis of 429 bp of the 16S rRNA gene as described previously [30]. Anaplasma capra-positive isolates were genetically profiled by the amplification of a longer fragment of 16S rRNA (rrs) gene as well as partial sequences of citrate synthase (gltA), heat-shock protein (groEL), major surface protein 2 (msp2) and major surface protein 4 (msp4) genes as described previously (Table 1).…”
Section: Dna Extraction and Pcr Amplificationmentioning
confidence: 99%
“…In previous studies, several Anaplasma spp. were detected in cervids from Korea such as A. phagocytophilum (89/266 pools, 24.5%) and A. bovis (20/266 pools, 5.5%) in ticks collected from KWD [ 15 ]; A. phagocytophilum (42/66, 63.6%) and A. bovis (23/66, 34.8%) in KWD from Chungbuk, Gangwon, Gyeonggi, Jeonnam and Ulsan Provinces [ 16 ]; A. phagocytophilum (4/10, 40%) in KWD from Jeonbuk Province [ 30 ] and A. bovis in one Korean spotted deer ( Cervus nippon ) from Joenbuk Province [ 21 ]. This is the first molecular detection of Anaplasma spp.…”
mentioning
confidence: 99%